Sigma Receptors as Endoplasmic Reticulum Stress “Gatekeepers” and their Modulators as Emerging New Weapons in the Fight Against Cancer - Tesei, Anna; Cortesi, Michela; Zamagni, Alice; Arienti, Chiara; Pignatta, Sara; Zanoni, Michele; Paolillo, Mayra; Curti, Daniela; Rui, Marta; Rossi, Daniela; Collina, Simona (Frontiers in Pharmacology, 2018)
Despite the interest aroused by sigma receptors (SRs) in the area of oncology, their role in tumor biology remains enigmatic. The predominant subcellular localization and main site of activity of SRs is the endoplasmic reticulum (ER). Current literature data, including recent findings on the sigma 2 receptor subtype (S2R) identity, suggest that SRs may play a role as (ER) stress gatekeepers. Although SR endogenous ligands are still unknown, a wide series of structurally unrelated compounds able to bind SRs have been identified. Currently, the identification of novel antiproliferative molecules acting via SR interaction is a challenging task for both academia and industry, as shown by the fact that novel anticancer drugs targeting SRs are in the preclinical-stage pipeline of pharmaceutical companies (i.e. Anavex Corp. and Accuronix). So far, no clinically available anticancer drugs targeting SRs are still available. The present review focuses literature advancements and provides a state-of-the-art overview of SRs, with emphasis on their involvement in cancer biology and on the role of SR modulators as anticancer agents. Findings from preclinical studies on novel anticancer drugs targeting SRs are presented in brief.